Realizing Strategic Approach in E-mail Marketing - A. S. Melekhova (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
E-mail marketing in line with context advertising, SMM, SEO-promotion and SERM are tools of digital communication. They provide shaping of stable long-term and regular communication (adjustment, support and retain) with potential and real customers (subscribers) of business, which explains topicality of the research subject. The use of digital information-communication technologies fosters customer base growth and building long-term relations with clients, which forms foundation for business extension and development. The article explains such notions as ‘E-mail marketing’, ‘eDM mail-outs’, ‘strategic approach’, ‘components of strategic approach’, systematizes types of mail-outs, describes specific features of content-plans of different types of mail-outs and gives practical recommendations for their use. Apart from that the author substantiates the idea that e-mail marketing is a promising and widely used trend in advertising and marketing, an effective tool of promotion in conditions of fast changing market environment and that it requires strategic approach to attain the set parameters of efficiency